The Combination of Black Soybean Tempeh and Purple Sweet Potato Affect Reactive Oxygen Species and Malondialdehyde Level in Streptozotocin-Induced Diabetic Rats - Eka Pratama Putri; Sri Rahayu Lestari; Abdul Gofur (Majalah Obat Tradisional, 2020)
Hyperglycemia conditions increase free radicals in the body that cause oxidative stress. Oxidative stress increase lipid peroxidation activity and reactive oxygen species (ROS). An antioxidant can prevent a free radical movement. The materials that contain potent antioxidants are black soybeans tempeh (BST) and purple sweet potatoes (PSP). The antioxidants in the BST are isoflavones with their derivates, and PSP is anthocyanins. This study aimed to determine the effect of BST and PSP extract on reactive oxygen species (ROS) and malondialdehyde (MDA) levels. In this study, rats were given a high-fat diet, 10% sucrose drink, and injected with multiple low-dose streptozotocin to induce T2DM. The animal's experiment divided into six groups: healthy rats, DM rats, DM rats + glibenclamide, DM rats + combination of BST and PSP in 3:1, 1:1, and 1:3 respectively. ROS levels were determined using the ELISA method and MDA levels were determined using spectrophotometer according to Thiobarbituric Acid (TBA) method. Our result suggests that the combination of BST and PSP significantly reduces ROS and MDA levels.